FAKTOR RESIKO YANG MEMPENGARUHI ONLINE PURCHASE INTENTION YANG DIMEDIASI OLEH TRUST PADA MASYARAKAT KOTA BATAM - Raymond Raymond; Renza Fahlevi; Fitriana Aidnilla Sinambela (POLITEKNIK LP3I JAKARTA, 2024)
The purpose of this study is to analyze and show the influence of risk factors on the trust of the Batam city community which affects online shopping intentions. This research is quantitative in nature. The population of this research is consumers buying goods through online stores. The sample size of this study was 209 respondents. This research data processing uses the SmartPLS application. The data for this study were obtained from primary and secondary sources, primary data were obtained through questionnaires while secondary data were obtained from sources already available from journals, bulletins, and data from the internet. In analyzing the data, researchers used descriptive analysis methods to analyze respondent demographics and quantitative analysis to test variables and relationships between variables using SPSS. The result of this study is that there is a significant positive influence between financial risk, product risk, social risk, security risk and time risk with trust on Online Purchase Intention in Batam. Trust affects online purchase Intention, when trust can be an intermediary that causes consumers' desire to shop in e-commerce, when the higher the level of store trust can affect consumer confidence as well as the resulting online purchase intention. Keywords: Risk, Online Purchase Intentions, Trust, Batam, e-commerce